The Impossible Sustainability of the Bay of Brest? Fifty Years of Ecosystem Changes, Interdisciplinary Knowledge Construction and Key Questions at the Science-Policy-Community Interface - Ragueneau, Olivier; Raimonet, Mélanie; Mazé, Camille; Coston-Guarini, Jennifer; Chauvaud, Laurent; Danto, Anatole; Grall, Jacques; Jean, Frédéric; Paulet, Yves-Marie; Thouzeau, Gérard (Frontiers in Marine Science, 2018)
In this contribution, the study of the Bay of Brest ecosystem changes over the past 50 years is used to explore the construction of interdisciplinary knowledge and raise key questions that now need to be tackled at the science-policy-communities interface. The Bay of Brest is subject to a combination of several aspects of global change, including excessive nutrient inputs from watersheds and the proliferation of invasive species. These perturbations strongly interact, affecting positively or negatively the ecosystem functioning, with important impacts on human activities. We first relate a cascade of events over these five decades, linking farming activities, nitrogen and silicon biogeochemical cycles, hydrodynamics of the Bay, the proliferation of an exotic benthic suspension feeder, the development of the Great scallop fisheries and the high biodiversity in maerl beds. The cascade leads to today’s situation where toxic phytoplankton blooms become recurrent in the Bay, preventing the fishery of the great scallop and forcing the fishermen community to switch pray and alter the maerl habitat and the benthic biodiversity it hosts, despite the many scientific alerts and the protection of this habitat. In the second section, we relate the construction of the interdisciplinary knowledge without which scientists would never have been able to describe these changes in the Bay. Interdisciplinarity, first among natural sciences (NS) and then, between natural sciences and human and social sciences (HSS). We finally ask key questions at the science-policy interface regarding this unsustainable trend of the Bay: How is this possible, despite decades of joint work between scientists and fishermen? Is adaptive co-management a sufficient condition for a sustainable management of an ecosystem? How do the different groups (i.e. farmers, fishermen, scientists, environmentalists), with their diverse interests, take charge of this situation? What is the role of power in this difficult transformation to sustainability? Combining natural sciences with political science, anthropology and the political sociology of science, we hope to improve the contribution of HSS to integrated studies of social-ecological systems, creating the conditions to address these key questions at the science-policy interface to facilitate the transformation of the Bay of Brest ecosystem towards sustainability.